Doctrinal differences of the states-members European Union in the management of concentration through mergers and acquisitions of companies - Андрущенко, І. Г. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
The article is devoted to the legal framework for regulation of mergers and acquisitions in the states-members EU. Consider individual differences in doctrinal views on the process of formation of companies, as well as provides comparative characteristics of law companies in continental Europe and Great Britain.